IMPLEMENTASI PRINSIP-PRINSIP EKONOMI SYARIAH DALAM AKTIVITAS PRODUKSI - Jamaluddin; Nur Ifna; Anwar Enre (Fakultas Agama Islam Universitas Cokroaminoto Makassar, 2022)
The research aims to analyze the implementation of sharia economic principles in production activities. The type of research used is library research, using a research approach, namely economic sociology and a normative theological approach. The results of the research show that production in Islamic economics must be based on principles that have been agreed upon by Islamic economic figures and scientists. Production activities carried out by a person or company/institution must apply the principles of monotheism, justice, mashlahah, trust, balance, and ta'awun. The principle of monotheism leads to the closeness of producers to their creators, justice and balance will create peace, mashlahah creates a happy life, trustworthiness improves relations with others, while ta'awun contains the value of social concern for fellow creatures.